Undifferentiated Spindle-Cell Carcinoma of the Gallbladder: A Report of a Case, an Immunohistochemistry Profile, and a Review of the Literature - Kabir Bolarinwa Badmos; Laila Salah Seada; Fawaz Fahad Al Rashid; Hanan Abdulhafez Oreiby (Case Reports in Pathology)
Undifferentiated spindle-cell carcinoma is a rare gallbladder cancer with a worse or similar prognosis to the generally dismal outcome seen in most gallbladder cancer patients. We reported a case of SpCC, stage IV disease that was initially diagnosed as undifferentiated pleomorphic sarcoma, but deeper sections revealed few clusters of epithelioid clear cells. Although the tumour showed biphasic appearances on haematoxylin and eosin, it exhibited poor protein expression with most sarcoma markers being negative except for focal vimentin positivity. The CEA and CK7 were positive only in the epithelioid clear cell clusters while CD 68 positive was also focally positive in the spindle-cell component. The poor tumour differentiation coupled with advanced stage at presentation was partly responsible for the disease progression and patients' death one year after surgery. Early diagnosis and surgical intervention with better understanding of this tumour biology may offer improved prognosis and survival in this rare cancer.